2020
DOI: 10.1080/10717544.2020.1760961
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of candesartan loaded self-nanoemulsifying drug delivery system for improving its dissolution rate and pharmacodynamic potential

Abstract: During the last decades, much attention has been focused on SNEDDS approach to resolve concerns of BCS II class drugs with accentuation on upgrading the solubility and bioavailability. The present hypothesis confirms the theory that SNEDDS can reduce the impact of food on Candesartan solubilization, thereby offering the potential for improved oral delivery without co-administration with meals. The present studies describe quality-by-design-based development and characterization of Candesartan loaded SNEDDS for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Solubility studies of the drug in the lipid help in determining the encapsulating index of a drug in the lipid nanoparticles. There is a direct relationship existing between drug solubility and encapsulation efficiency (Makoni and Ranchhod, 2020 ; Verma and Kaushik, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Solubility studies of the drug in the lipid help in determining the encapsulating index of a drug in the lipid nanoparticles. There is a direct relationship existing between drug solubility and encapsulation efficiency (Makoni and Ranchhod, 2020 ; Verma and Kaushik, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…It was found, which confirmed its clarity after dispersion into distilled water. Also, it confirmed that there are no chances of drug precipitation and optimized formulation had good solubilization capacity after dispersion ( Verma and Kaushik, 2020 ).…”
Section: Discussionmentioning
confidence: 70%
“…Droplet size is of the primary essential qualities of nanoemulsion for stability assessment and a fundamental advance in improving assimilation of medicament. Its smaller size results in greater interfacial surface area for assimilation of medicament and enhanced bioavailability and pharmacological effect ( Verma and Kaushik, 2020 ). The higher the ratio of surfactant and co-surfactant concentration, the lower the droplet size produced ( Kadu et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…56 Each 550 mg of SNEDDS was supplemented with both media (36 mL), the formula of which is shown in Table 1. 57,58 Compositions of Ca 2+ , bile salt (BS),…”
Section: Dynamic In Vitro Lipolysis Study For Investigation Of Food Imentioning
confidence: 99%